2019
DOI: 10.24106/kefdergi.3776
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi Öğretmenlerinin Üstün Yetenekli Çocuklara Yönelik Algı ve Eğitim İhtiyaçlarının Belirlenmesi

Abstract: ÖzBu araştırmada, okul öncesi öğretmenlerinin üstün yetenekli öğrencilere yönelik algıları ve eğitim ihtiyaçlarının belirlenmesi amaçlanmıştır. Tarama modeli niteliğinde olan araştırmanın evreni Kuzey Kıbrıs'ta Milli Eğitim ve Kültür Bakanlığı İlköğretim kademesinde olan 99 ilköğretim okulunda ve 13 anaokulunda görev yapan okul öncesi öğretmenleri oluştururken, ölçek ve anketi hatasız doldurulan 100 okul öncesi öğretmeni araştırmanın örneklemini oluşturmaktadır. Veri toplama aracı olarak Demirok ve Özcan taraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
(5 reference statements)
1
7
0
7
Order By: Relevance
“…The needs of primary school teachers regarding the education of gifted students do not differ significantly according to age and professional seniority variables. In similar studies in our country, Mavi (2017) counselor teachers, Sak (2011) mathematics teachers, Gülkaya (2016) preschool teachers have concluded that they feel inadequate and need training about gifted education.…”
Section: Wwwturkishstudiesnet/educationmentioning
confidence: 83%
See 4 more Smart Citations
“…The needs of primary school teachers regarding the education of gifted students do not differ significantly according to age and professional seniority variables. In similar studies in our country, Mavi (2017) counselor teachers, Sak (2011) mathematics teachers, Gülkaya (2016) preschool teachers have concluded that they feel inadequate and need training about gifted education.…”
Section: Wwwturkishstudiesnet/educationmentioning
confidence: 83%
“…In similar studies conducted in our country, Güneş (2015), Sönmez (2017) and Tortop and Kunt (2013) primary school teachers, Kunt (2012) science and technology teachers, and Şişman (2018) mathematics teachers' attitudes towards the education of gifted students were undecided level. In addition, Daştan (2016) and Gülkaya (2016) stated that preschool teachers had a moderate positive attitude towards the education of gifted students, while Sarar (2018) and Seyhan (2015) stated that preschool teachers had a high level of attitude.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations